Examining bureaucratic performance of South African local government: local municipalities in Limpopo province - Mamogale, Majuta Judas (My University, 2016)
In democratic South Africa, power regarding the provision of public goods and services is decentralised to local government level simply because municipalities are the coalface of service delivery and are closer to the people than national and provincial spheres of government. As a result, municipalities are assigned service delivery responsibilities by the Constitution. To discharge these constitutional responsibilities and functions in terms of public goods and service provision effectively and efficiently, municipalities are, firstly, expected to have high institutional capacity to deliver and be held accountable to their municipal councils and to behave in a fiscally responsible manner. Secondly, they are further expected to be characterised by strong and powerful municipal councils to exercise their formal powers of oversight function over municipal administration. Despite huge and continuous resource investment in terms of funding and capacity building and training interventions from the centre to build and strengthen the local government capacity to fulfil its public goods and service delivery responsibilities, South African local government, with specific reference to Limpopo local government, continues to be afflicted by persistent poor bureaucratic performance in relation to water and sanitation provision as well as financial management. In Limpopo Province, there are, however, a very few pockets of good performance (e.g. the Waterberg District Municipality) pertaining to financial management. Generally, manifestation of these governance problems is illustrated by high rates of negative audit outcomes, high levels of underspending, high levels of financial misconduct, high consumer debt and increasing sporadic community protests against poor municipal service delivery. Using a qualitative research approach and methods (i.e. interviews, observations, focus group discussions, questionnaire and document review), this study has explored the determinants of bureaucratic performance of South Africa’s local government with specific reference to Limpopo local government. A multiple qualitative case study approach, consisting of five municipalities (i.e. Capricorn and Waterberg District Municipalities, and Fetakgomo, Greater Tubatse and Greater Tzaneen Local Municipalities) was, thus, applied. This multiple case study approach assisted in enhancing the validity and reliability as well as replication of the study results to the entire system of Limpopo local government. Both purposive and random sampling techniques were used to sample the above mentioned five case studies and select the research participants. The added value of this study is, of course, the new dimension it has suggested such as theory of bureaucracy and the principal-agent model to explore and analyse the determinants of municipal bureaucratic performance in Limpopo Province. In effect, these two theories have rarely been tested together in analysing local government bureaucratic performance, but, in this study, they are used together to analyse the phenomena. In spite of their commonalities and variations, the study has discovered that not all bureaucratic performance failures within Limpopo local government are related to the lack of meritocracy, especially at managerial level. In effect, the level of meritocracy is very low at operational and implementation level in municipalities. The study, for example, has found that the percentage of the total municipal workforce with university or college qualifications at National Qualification Framework level 6 and above stood at 17 percent in the Greater Tubatse Municipality as compared to 58 percent and 76 percent in Fetakgomo and Greater Tzaneen Local Municipalities respectively. At the management level, the study, in contrast, found that the percentage of senior managers with professional qualifications at NQF level 6 and above stood at more than 80 percent in all the above-mentioned local municipalities. At the district level, the study further found that the percentage of total municipal workforce with university qualifications at NQF level 6 and above, as prescribed by municipal regulations on minimum competency level requirements and qualifications, stood at 7.4 percent and 59 percent respectively in the Capricorn and Waterberg District Municipalities in the period the study was undertaken. The study, however, has revealed serious paradoxes at management level regarding the possession of university qualifications by senior managers. For instance, the study found that the percentage of section 54A and 56 managers with professional qualifications at NQF level 6 and above in the Waterberg District Municipality was 86 percent as opposed to 33.3 percent in the Capricorn District Municipality. On the matter of the municipal council oversight function over municipal administration, the study findings confirmed the initial study proposition that strong and independent municipal councils, as opposed to weak or less-independent councils, play a vital role in determining bureaucratic quality or performance of municipalities. In effect, the study found that municipal councils or their council oversight committees in selected case studies were ineffective in exercising their formal powers of oversight. According to the study, the ineffectiveness of municipal council oversight committees was attributed to the following; institutional instability that characterised these municipalities between 2011 and 2014; the influence of political parties; or the prolonged and sustained single dominance of the municipal councils by one political party. Given the parliamentary governance system generally adopted by the South African state, the study further observed that municipal councils are effectively rendered inefficient by the fusion of both legislative and executive powers in the same person, being the municipal council. In contrast, this is, however, not the case in national and provincial spheres of government where the separation of powers between the legislature and the executive is clear and unambiguous compared with the local sphere of government. The study concluded that the persistent poor bureaucratic performance of South African local government, with specific reference to Limpopo local government, is as a result of none institutionalisation and none enforcement of a meritocratic recruitment culture at operational and implementation level as opposed to that at a management level. In addition, weak and less-independent municipal councils account for persistent poor bureaucratic performance of municipalities in Limpopo Province. If Limpopo local government is to become more developmental and meet the minimum service delivery expectations of communities, the study suggests that institutionalisation of meritocracy must be enforced by well-resourced and independent municipal councils vis-a-vis mayoral executive committees.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy (Public Management) at Wits school of governance Faculty of Commerce, Law and Management University of the Witwatersrand South Africa, 2016
Keywords: Municipal services--South Africa; Local government--South Africa; Comparative government